Apple Peel Deformity and Malrotation of Gut: Autopsy Findings of a Rare Cause of Mortality in Utero - Deepti MUTREJA; Sharanjit SINGH (Türk Patoloji Dergisi, 2022)

(untitled)
One-third of all intestinal obstructions in the newborn are caused by atresias. The most common site is the duodenum followed by jejunoileal and colonic locations. Herein we report the autopsy findings of a rare case of jejunoileal atresia associated with malrotation of gut. Autopsy performed on a 36 weeks old male fetus still birth, born of a non-consanguineous marriage, demonstrated jejunoileal atresia with apple peel deformity and malrotation of gut. Although the diagnosis was established in the prenatal period, in utero fetal demise occurred before definitive surgical intervention could be done. This case highlights the importance of early diagnosis and intervention.